2016
DOI: 10.1016/j.jaci.2016.06.033
|View full text |Cite
|
Sign up to set email alerts
|

Interleukins (from IL-1 to IL-38), interferons, transforming growth factor β, and TNF-α: Receptors, functions, and roles in diseases

Abstract: There have been extensive developments on cellular and molecular mechanisms of immune regulation in allergy, asthma, autoimmune diseases, tumor development, organ transplantation, and chronic infections during the last few years. Better understanding the functions, reciprocal regulation, and counterbalance of subsets of immune and inflammatory cells that interact through interleukins, interferons, TNF-α, and TGF-β offer opportunities for immune interventions and novel treatment modalities in the era of develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
617
1
30

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 702 publications
(702 citation statements)
references
References 217 publications
14
617
1
30
Order By: Relevance
“…Li et al reported an extracellular function of the IL-37 precusor, which suppresses LPS-induced IL-6 production in human M1 differentiated macrophages (49). IL-37 acts as an extracellular cytokine by binding to the IL-18 receptor and requires the IL-1 family decoy receptor IL-1R8 for its anti-inflammatory function (49) It has been shown that these pro-inflammatory cytokines (TNF-α, IL-1α, IL-1β, IFN-γ) could play pivotal roles in experimental autoimmune thyroiditis, multiple sclerosis, insulin-dependent diabetes mellitus or experimental autoimmune diabetogenesis, which may indirect suggest the biological and potentially therapeutic relevance of IL-37 to these diseases (50)(51)(52)(53)(54)(55). However, it remains unknown whether nuclear translocation of IL-37 is the only mechanism that leads to reduction in cytokine expressions.…”
Section: The Function Of Il-37mentioning
confidence: 99%
“…Li et al reported an extracellular function of the IL-37 precusor, which suppresses LPS-induced IL-6 production in human M1 differentiated macrophages (49). IL-37 acts as an extracellular cytokine by binding to the IL-18 receptor and requires the IL-1 family decoy receptor IL-1R8 for its anti-inflammatory function (49) It has been shown that these pro-inflammatory cytokines (TNF-α, IL-1α, IL-1β, IFN-γ) could play pivotal roles in experimental autoimmune thyroiditis, multiple sclerosis, insulin-dependent diabetes mellitus or experimental autoimmune diabetogenesis, which may indirect suggest the biological and potentially therapeutic relevance of IL-37 to these diseases (50)(51)(52)(53)(54)(55). However, it remains unknown whether nuclear translocation of IL-37 is the only mechanism that leads to reduction in cytokine expressions.…”
Section: The Function Of Il-37mentioning
confidence: 99%
“…There are 38 interleukins which are designated by the abbreviation IL (from Interleukin) and Arabic numbers [19]. Interleukins are produced by various types of body cells, wherein the speciic interleukins (IL-1) can be secreted by up to 20 diferent cell types.…”
Section: Interleukinsmentioning
confidence: 99%
“…The TGF-β family consists of TGF-β1, TGF-β2, and TGF-β3 which are produced by a variety of cells including fibroblasts, platelets, mast cells, monocytes, macrophages, and Tregs [135].…”
Section: Tgf-βmentioning
confidence: 99%